1997
DOI: 10.1897/1551-5028(1997)016<0059:eopitt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology of Pesticides in the Tropical Paddy Field Ecosystem

Abstract: Abstract-In tropical countries rice has been identified as one of the crops that is particularly susceptible to the negative impacts of pesticide use. In addition to the physicochemical nature of the pesticide, tropical climatic conditions and agricultural practices play important roles in determining the fate and distribution of pesticides in the tropical paddy field ecosystem. The assessment of ecotoxicological effects of pesticides in the tropical paddy field ecosystem has been based primarily on acute leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…All of the above-mentioned studies indicate negative impact of pesticides on earthworm growth and reproduction. Some studies also indicate that microorganisms in the soil help degrade the chemicals [74,75]. So, there is a need to acquire more knowledge on the chemical nature, mode of action, and means of degradation of pesticides in soil, so that harm caused to soil fauna as well as to organisms higher up in the food chain can be minimized.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…All of the above-mentioned studies indicate negative impact of pesticides on earthworm growth and reproduction. Some studies also indicate that microorganisms in the soil help degrade the chemicals [74,75]. So, there is a need to acquire more knowledge on the chemical nature, mode of action, and means of degradation of pesticides in soil, so that harm caused to soil fauna as well as to organisms higher up in the food chain can be minimized.…”
Section: Confounding Variablesmentioning
confidence: 99%
“…Seeding´1 to 1 2 Fertilizer application´1 to 5 6 Weed control´4 to 6 10 Pest control´4 to 6 10 Source: Questionnaire on Sustainability Practices survey 2012-2013.…”
Section: Farming Process Range Pointsmentioning
confidence: 99%
“…Study in Malaysia [5] indicated that heavy metals were found in paddy fields derived from the heavy use of fertilizers and pesticides as agrochemicals which are known to contain zinc, copper, lead and cadmium. In the tropical paddy field ecosystem, the heavy use of chemicals such as pesticides has affected the ecosystem of other nontarget organisms such as microalgae and cyanobacteria [6]. In order to examine the degree of sustainability in production practices, various studies which have assessed the production practices at farm level were reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in agricultural practices between temperate and tropical agricultural fields may be of great importance when comparing the fate and effects of pesticides (Sethunathan 1989;Abdullah et al 1997;Castillo et al 1997;Henriques et al 1997). For example, tropical aquatic agroecosystems have been reported to be especially at risk to the effects of agrochemicals because of the large amounts of runoff that occur during irrigation and episodes of increased tropical precipitation (Henriques et al 1997).…”
Section: Differences Between Temperate and Tropical Agricultural Areamentioning
confidence: 99%
“…The tropical paddy field ecosystem has also been identified as one of the major contributing agroecosystems from which pesticide residues contaminate the rest of the environment. This is attributed to the relatively large amounts of pesticides applied in the paddy fields, in addition to the common practice of draining the paddy water in irrigation canals that eventually flow into the freshwater system and then into the marine environment (Abdullah et al 1997). In this way, highly valued ecosystems in several tropical areas have been reported to be subject to pesticide contamination and their effects on several environmental components, e.g., lagoons and bays (Nicaragua: Carvalho et al 2002aCarvalho et al , 2003Mexico: Carvalho et al 2002b;Hernández-Romero et al 2004;Florida bay: Scott et al 2002;India: Pandit et al 2006;Sri Lanka: Guruge and Tanabe 2001;Vietnam: Nhan et al 1999) and mangrove forests, seagrass beds and coral reefs (Australia: Bell and Duke 2005;Duke et al 2005).…”
Section: Differences Between Temperate and Tropical Agricultural Areamentioning
confidence: 99%